Circular ANRIL isoforms switch from repressors to activators of p15/CDKN2B expression during RAF1 oncogene-induced senescence - Muniz, Lisa (RNA Biol, 2020)
Long non-coding RNAs (ncRNAs) are major regulators of gene expression and cell fate. The INK4 locus encodes the tumour suppressor proteins p15(INK4b), p16(INK4a) and p14(ARF) required for cell cycle arrest and whose expression increases during senescence. ANRIL is a ncRNA antisense to the p15 gene. In proliferative cells, ANRIL prevents senescence by repressing INK4 genes through the recruitment of Polycomb-group proteins. In models of replicative and RASval12 oncogene-induced senescence (OIS), the expression of ANRIL and Polycomb proteins decreases, thus allowing INK4 derepression. Here, we found in a model of RAF1 OIS that ANRIL expression rather increases, due in particular to an increased stability. This led us to search for circular ANRIL isoforms, as circular RNAs are rather stable species. We found that the expression of two circular ANRIL increases in several OIS models (RAF1, MEK1 and BRAF). In proliferative cells, they repress p15 expression, while in RAF1 OIS, they promote full induction of p15, p16 and p14(ARF) expression. Further analysis of one of these circular ANRIL shows that it interacts with Polycomb proteins and decreases EZH2 Polycomb protein localization and H3K27me3 at the p15 and p16 promoters, respectively. We propose that changes in the ratio between Polycomb proteins and circular ANRIL isoforms allow these isoforms to switch from repressors of p15 gene to activators of all INK4 genes in RAF1 OIS. Our data reveal that regulation of ANRIL expression depends on the senescence inducer and underline the importance of circular ANRIL in the regulation of INK4 gene expression and senescence.